Mycenaean wall painting in context: new discoveries, old finds reconsidered : [proceedings of an International Workshop held February 10-11, 2011 at the National Hellenic Research Foundation ...] - Mprekulakē, Charikleia; Davis, Jack Lee; Stocker, Sharon R. (Meletēmata, 2015)
During the recent decades many new Mycenaean wall paintings have been brought to light and older finds have been restored and reconstructed afresh in light of newly found joining fragments. These paintings derive both from palatial and non-palatial contexts, from major centers on the mainland (including Mycenae, Tiryns, Argos, Pylos, Thebes, Orchomenos, and Gla) and from recently excavated sites, such as Iklaina in Messenia. However, in contrast to the corpora of Minoan and Cycladic wall paintings, Mycenaean paintings have survived in poor physical condition. For the most part, they are highly fragmentary and lack iconographic and contextual coherence. The present book, lavishly illustrated, including many full-page details, offers an up to date insight into new discoveries of Mycenaean wall painting and new iconographic interpretations of old material, excavated long ago but never properly published. It is therefore likely to fill a large gap in our knowledge of Mycenaean wall painting and Aegean wall painting in general, and help us to gain a better understanding of the visual language of Mycenaean painting and of how it was employed in the murals that adorned Mycenaean buildings